2012
DOI: 10.1007/s11420-012-9296-6
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Use of Functional Hip Motions on Localization of the Center of the Hip

Abstract: Background: The hip joint is generally considered a balland-socket joint, the center of which is used as an anatomic landmark in functional analyses and by surgical navigation systems. The location of the hip center has been estimated using functional techniques using various limb motions. However, it is not clear which specific motions best predicted the functional center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although full capsular repairs could be effective for larger capsulotomies or overresected cams, 31,79 closures should always be performed with extreme caution so as to not overtighten the capsule and exchange instability for joint tightness. The translations of the hip joint center of rotation 17,73 should be examined in the future to help characterize microinstability over the series of surgical stages. Furthermore, the balance between capsular repair and plication should be further examined to establish objective measures to minimize iatrogenic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Although full capsular repairs could be effective for larger capsulotomies or overresected cams, 31,79 closures should always be performed with extreme caution so as to not overtighten the capsule and exchange instability for joint tightness. The translations of the hip joint center of rotation 17,73 should be examined in the future to help characterize microinstability over the series of surgical stages. Furthermore, the balance between capsular repair and plication should be further examined to establish objective measures to minimize iatrogenic instability.…”
Section: Discussionmentioning
confidence: 99%
“…One error in determination of HJC location using image-based techniques is caused by the assumption of the femoral head as a sphere although it is not perfectly spherical. The use of image-based determination of the HJC is limited as MRI-based techniques require expensive medical imaging and the other modalities in this category expose the subject to ionizing radiation [7,8]. Predictive methods estimate the HJC based on regression equations between palpable bony landmarks and the joint centre [8].…”
Section: Motivationmentioning
confidence: 99%
“…In general, coordinate transformation techniques have been reported to be more accurate and much less sensitive to noise compared to sphere fitting techniques. Ehrig et al reported that the SCoRE algorithm is the most accurate transformation technique[7,23].…”
mentioning
confidence: 99%